Synthesis and characterization of alkyl- and acyl-substituted oxime-phosphazenes - Çil, E; Arslan, M; Görgülü, A (Natl Research Council Canada, 2005)
Two oxime-cyclophosphazenes were prepared from the hexakis(4-formylphenoxy)cyclotriphosphazene (2) and hexakis(4-acetylphenoxy)cyclotriphosphazene (8). The reactions of these oximes with ethyl bromide, allyl bromide, propanoyl chloride, and acriloyl chloride were studied. Hexasubstituted compounds were obtained from the reactions of hexakis{4-[(hydroxyimino)methyl]phenoxy}cyclotriphosphazene (3) with ethyl bromide (4), allyl bromide (5), and propanoyl chloride (6), however, the oxime groups on 3 rearranged to nitrile (7) in the reaction of 3 with acriloyl chloride. Hexasubstituted compounds were also obtained from the reactions of hexakis{4-[(1)-N-hydroxyethaneimidoyl]phenoxy}cyclotriphosphazene (9) with allyl bromide (11) and propanoyl chloride (12). Tetra- and penta-substituted products were obtained from the reactions of 9 with ethyl bromide (10) and acriloyl chloride (13), respectively. All products were generally obtained in high yields. The structures of the compounds were defined by elemental analysis, IR, H-1, C-13, and P-31 NMR spectroscopy.
Keywords: hexachlorocyclotriphosphazene; phosphazene; oxime; oxime derivatives; oxime-phosphazenes